Ilmu Pengetahuan dalam Perspektif Islam Berdasarkan Surat Al-Mujadalah Ayat 11 - Regina Yustisia; M. A Tihami; Siti Patimah; Wasehudin (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to understand the concept of knowledge from an Islamic perspective based on Surah Al-Mujadalah, verse 11. The verse emphasizes that Allah will elevate the ranks of believers who possess knowledge. This research was conducted using a qualitative method with a library research approach, analyzing various literatures, classical tafsir works, and scholars' perspectives to gain an in-depth understanding of the value of knowledge in Islam. The findings indicate that Surah Al-Mujadalah, verse 11 teaches the importance of knowledge as an element that elevates one's status in the sight of Allah, both spiritually and socially. The verse highlights the ethical value in social interactions, where believers and knowledgeable individuals are expected to display inclusiveness and respect for others. Additionally, Islam encourages the application of knowledge, as knowledge that is not practiced is considered futile and loses its blessings.